Interactions between the helminth and intestinal microbiome in smallholder chicken farming systems - Nemathaga, Mishumo; Smith, Rae M.; Malatji, Dikeledi P. (Frontiers in Veterinary Science, 2023)
Helminth parasite infections are widespread in smallholder farming systems affecting farmers and livestock animals. There are pathogenic parasites that populate the gut of their host and coexist closely with the gut microbiota. The physical and immunological environment of the gut can be modified by parasites and microbiota creating a wide range of interactions. These interactions modify the development of infection, affects overall host health, and can modify the way a host interacts with its bacterial microbiota. In addition, where there is a high worm burden parasites will affect the health of the host and intestinal tract colonization. This review highlights key studies on the interaction between helminth parasites and the intestinal microbiome to understand the relationship parasitic worm infections and gut microbiome health in chickens. Finally, the review discusses modulations, molecular changes, and the importance of helminth-microbiome interactions for the host.